Adaptation of a System of Treatment for Substance Use Disorders During the COVID-19 Pandemic. Issue 6 (November 2021) - Komaromy, Miriam; Tomanovich, Mary; Taylor, Jessica L.; Ruiz-Mercado, Glorimar; Kimmel, Simeon D.; Bagley, Sarah M.; Saia, Kelley M.; Costello, Eileen; Park, Tae Woo; LaBelle, Colleen; Weinstein, Zoe; Walley, Alexander Y.
Abstract : N/A: The Grayken Center for Addiction at Boston Medical Center includes programs across the care continuum for people with substance use disorders (SUDs), serving both inpatients and outpatients. These programs had to innovate quickly during the COVID-19 outbreak to maintain access to care. Federal and state regulatory flexibility allowed these programs to initiate treatment for people experiencing homelessness and maximize patient safety through physical distancing practices. Programs switched to telehealth with high levels of acceptability and patient retention. Some programs also maintained some face-to-face clinic visits to see patients with complex problems and to provide injectable medications. Text-messaging proved invaluable with adolescent and young adult clients, and a mobile-health outreach program was initiated to reach mother/child dyads affected by SUDs. A 24-hour hotline was implemented to support seamless access to treatment for hundreds released from incarceration early due to the pandemic. Boston Medical Center also launched the COVID Recuperation Unit to allow patients experiencing homelessness to recover from mild to moderate COVID-19 infection in an environment that took a harm-reduction approach to SUDs and provided rapid initiation of medication treatment. Many of these innovations increased access to treatment and retention of patients during the pandemic. Maintaining the revised regulations would allow flexibility to provide telehealth, extended prescriptions, and remote access to buprenorphine initiation to support and engage more patients with SUDs.